An assessment of qualified lifeguards' knowledge and attitudes towards AEDs in Singapore - Lim, Ming Han (2016)
Background of study: The Automated External Defibrillator (AED) is a fundamental equipment for basic life support (European Resuscitation Council [ERC], 2010). Each minute of cardiac arrest without defibrillation decreases survival chance by 10%. (US National Heart, Lung and Blood Institute, 2011). However, lifeguards in Singapore do not need AED certification to work (Tai, 2013). This may pose a threat to the lives of potential victims. Purpose of Study: To assess qualified Lifeguards’ knowledge and attitudes towards AEDs in Singapore. Methods: A non-experimental, cross-sectional hardcopy survey was used for this investigation. 156 valid surveys were collected through on-site visits carried out at 12 facilities over a 3-week period. Results: 36.5% of participants were not AED-trained, and among those AED-trained, 29.3% did not hold valid certifications. Confidence in using an AED during emergencies was moderate with a mean of 3.05±1.33 (Likert-scale 1-5), and 67.3% incorrectly believed that AED usage could harm an unconscious victim. 30.1% were unwilling to use an AED on a stranger when off-duty. After being informed that they were protected from liability, 76.3% of participants felt more inclined to use an AED on strangers when off-duty. Conclusions: Lifeguards in Singapore generally have poor knowledge on AEDs, a negative attitude towards AED usage and are poorly informed on AED and lifesaving legislation. Making AED certification compulsory for lifeguards would likely increase their confidence in using AEDs. Clarification regarding protection from legal liability should be provided to increase lifeguards’ willingness to use AEDs.